2012
DOI: 10.5301/jn.5000135
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient supplementation in maintenance haemodialysis patients enhances activity of antioxidant enzymes

Abstract: These results are consistent with a beneficial effect of the cocktail on antioxidant enzyme activity and may contribute to an indication for large-scale studies to assess clinical outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Patients with CKD have decreased plasma vitamin C and E concentrations [32,33,34]. Oral supplementation of vitamins C and E, in combination [35,36], or as a micronutrient cocktail containing physiologic doses of antioxidant vitamins and trace minerals [36], can decrease oxidative stress in humans. The majority of studies investigating anti-oxidant treatments in CKD patients show a reduction in oxidative stress and many show improved renal function (reviewed in References [37,38]).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD have decreased plasma vitamin C and E concentrations [32,33,34]. Oral supplementation of vitamins C and E, in combination [35,36], or as a micronutrient cocktail containing physiologic doses of antioxidant vitamins and trace minerals [36], can decrease oxidative stress in humans. The majority of studies investigating anti-oxidant treatments in CKD patients show a reduction in oxidative stress and many show improved renal function (reviewed in References [37,38]).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E levels were higher in healthy subjects compared with subjects in all other stages of renal function decline [ 26 ]. Oral supplementation of vitamins C and E, in combination [ 27 , 28 ], or as a micronutrient cocktail containing physiologic doses of antioxidant vitamins and trace minerals [ 28 ], can decrease oxidative stress in humans. Using rats, others have shown that vitamin E ameliorates the decline in GFR associated with aging and oxidative stress [ 29 ], and that co-supplementation of vitamins E and C prevents gentamicin-induced nephrotoxicity and preserves GFR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral supplementation with vitamins C and E, in combination [ 27 , 28 ], or as a micronutrient cocktail containing physiologic doses of antioxidant vitamins and trace minerals [ 28 ], can decrease oxidative stress in humans. In human CKD patients, oxidative stress is common and considered to be an important pathogenic mechanism [ 29 ].…”
Section: Discussionmentioning
confidence: 99%